Thrombophlebitis at infusion sites in surgical ward: a clinical study - Dwivedi, Rajeev; Singh, Atul Kumar; Gaharwar, A. P. S. (International Surgery Journal, 2018)
Background: Peripheral venous Cannulation is indispensable in admitted patients in surgical ward, thrombophlebitis following infusion is seldom serious, but it effects on postoperative recovery, hospital stay and hence burden of disease are magnanimous. The objective of the study to know the common sites of thrombophlebitis, Frequency of thrombophlebitis in relations to type of fluid and drugs used, and to find out the incidence of thrombophlebitis in relation to diseased condition and type of surgical patient. Methods: this prospective observational study was conducted on 300 patients admitted in surgical ward of S.S Medical College and associated S.G.M. hospital, Rewa (M.P.) patients selected randomly. These Patients were visited daily for any sign and symptoms at infusion site. The incidence of thrombophlebitis according to common infusion sites, in relations to type of fluid and drugs used and in relation to diseased condition and type of surgical patients were recorded. The tool designed to collect the data were sociodemographic Performa and observational check list. Results: In total 300 patients the incidence of thrombophlebits is highest (100%) in Saphenous vein (Lower Limb) minimum (17%) in Basilicvein (Upper Limb). Incidence of thrombophlebitis is higher in earlier days (within 2 days) of infusion with Dextrose containing fluid (D5%+ D10%) and higher in critically ill and emergency operated patients. Conclusions: Thrombophelebitis is still an important ongoing problem in admitted patients in surgical ward. Incidence is highest in saphenous vein, with dextrose containing fluid and in critically ill & emergency operated patients. It has definite relationship with site of infusion site, type of fluid, illness of patients and nature of operation